Kualitas tidur sebagai faktor risiko peningkatan tekanan darah pada remaja - Arie Taufansyah Putra Nasution; Rafita Ramayanti; Oke Rina Ramayani; Rosmayanti Siregar; Beatrix Siregar (Fakultas Kedokteran USU, 2014)
Hypertension in adolescent must be awared, because adolescent with hypertension has higher risk of morbidity and mortality. Hypertension can be influenced by poor sleep quality, so early detection of hypertension and sleep quality in adolescent is needed.Keywords : adolescents; blood pressure; sleep quality